Clopidogrel significantly lowers the development of atherosclerosis in ApoE-deficient mice in vivo - Heim, Christian; Gebhardt, Julia; Ramsperger-Gleixner, Martina; Jacobi, Johannes; Weyand, Michael; Ensminger, Stephan M. (Heart and Vessels, 2016)
The anti-platelet drug clopidogrel has been shown to modulate adhesion molecule and cytokine expression, both playing an important role in the pathogenesis of atherosclerosis. The aim of this study was to investigate the impact of clopidogrel on the development and progression of atherosclerosis. ApoE(-/-) mice fed an atherogenic diet (cholesterol: 1 %) for 6 months received a daily dose of clopidogrel (1 mg/kg) by i.p. injection. Anti-platelet treatment was started immediately in one experimental group, and in another group clopidogrel was started 2 month after beginning of the atherogenic diet. Blood was analysed at days 30, 60 and 120 to monitor the lipid profile. After 6 months the aortic arch and brachiocephalic artery were analysed by Sudan IV staining for plaque size and by morphometry for luminal occlusion. Serum levels of various adhesion molecules were investigated by ELISA and the cellular infiltrate was analysed by immunofluorescence. After daily treatment with 1 mg/kg clopidogrel mice showed a significant reduction of atherosclerotic lesions in the thoracic aorta and within cross sections of the aortic arch [plaque formation 55.2 % (clopidogrel/start) vs. 76.5 % (untreated control) n = 8, P < 0.05]. After treatment with clopidogrel P-/E-selectin levels and cytokine levels of MCP-1 and PDGF? were significantly reduced as compared to controls. The cellular infiltrate showed significantly reduced macrophage and T-cell infiltration in clopidogrel-treated animals. These results show that clopidogrel can effectively delay the development and progression of 'de-novo' atherosclerosis. However, once atherosclerotic lesions were already present, anti-platelet treatment alone did not result in reverse remodelling of these lesions.
EVALuna2:16107